PENGEMBANGAN NASIONALISME DALAM KEARIFAN LOKAL MASYARAKAT ACEH YANG MENJALANKAN SYARIAT ISLAM - Sulaiman .; Nurmasyitah . (Universitas Syiah Kuala, 2020)
The people of Aceh, in its history until now. considered a strong adherent of Islam. Islam has not only been strived to be upheld in the midst of society in terms of the implementation of its teachings, this religion has also become the main foundation in the formation of nationalist attitudes, the tradition of the royal court in the past is full of Islamic values, since the title used, the concept of governance , court ceremonial traditions (which do not differentiate between Islamic and royal traditions). and various royal religious policies, especially in the 17th century. Islam was not only an inspiration for development and progress in Aceh in various fields, it also played a major role in the strong resistance against the Portuguese in Malacca. in the first half of the 16th century, and the Netherlands, in the late 19th and early 20th centuries. This war in the name of religion has always been held closely by the community consistently.